2020
DOI: 10.5194/acp-20-9183-2020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular understanding of new-particle formation from α-pinene between −50 and +25 °C

Abstract: Abstract. Highly oxygenated organic molecules (HOMs) contribute substantially to the formation and growth of atmospheric aerosol particles, which affect air quality, human health and Earth's climate. HOMs are formed by rapid, gas-phase autoxidation of volatile organic compounds (VOCs) such as α-pinene, the most abundant monoterpene in the atmosphere. Due to their abundance and low volatility, HOMs can play an important role in new-particle formation (NPF) and the early growth of atmospheric aerosols, even with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 94 publications
0
70
0
Order By: Relevance
“…C 18 Oleic acid, linoleic acid and linolenic acid are the most commonly found unsaturated FAs in macro algae. FAs with a carbon chain shorter than C 20 were used by atmospheric chemists as organic tracers of atmospheric aerosols from microbe or kitchen emission (Simoneit and Mazurek, 1982;Zheng et al, 2000;Guo et al, 2003;Rogge et al, 1991;DeMott et al, 2018;Willoughby et al, 2016). In our study, no saturated FAs were detected in 10-18 nm particles.…”
Section: Fatty Acidsmentioning
confidence: 52%
“…C 18 Oleic acid, linoleic acid and linolenic acid are the most commonly found unsaturated FAs in macro algae. FAs with a carbon chain shorter than C 20 were used by atmospheric chemists as organic tracers of atmospheric aerosols from microbe or kitchen emission (Simoneit and Mazurek, 1982;Zheng et al, 2000;Guo et al, 2003;Rogge et al, 1991;DeMott et al, 2018;Willoughby et al, 2016). In our study, no saturated FAs were detected in 10-18 nm particles.…”
Section: Fatty Acidsmentioning
confidence: 52%
“…This provides a framework for incorporating a comprehensive description of pure biogenic nucleation into a global model and, ultimately, allowing for a more rigorous description of aerosol formation and the climatic consequences. α-Pinene is considered as it is the most widely studied and widely emitted monoterpene (∼ 32 Tg yr −1 ; Sindelarova et al, 2014) and, with measured HOM yields of around 3 %-10 % (Ehn et al, 2014;Jokinen et al, 2015), has the potential to produce 2-7 Tg HOM yr −1 with the range arising from uncertainties in emissions, HOM yield, and difference in mass between the precursor biogenic volatile organic compounds (BVOC) and the HOMs, which will have at least six additional oxygen atoms but, in some cases, considerably more. HOM yields from β-pinene (the second most widely emitted monoterpene; Sindelarova et al, 2014) and isoprene (the most widely emitted BVOC; Sindelarova et al, 2014) are negligible (Ehn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…α-Pinene is considered as it is the most widely studied and widely emitted monoterpene (∼ 32 Tg yr −1 ; Sindelarova et al, 2014) and, with measured HOM yields of around 3 %-10 % (Ehn et al, 2014;Jokinen et al, 2015), has the potential to produce 2-7 Tg HOM yr −1 with the range arising from uncertainties in emissions, HOM yield, and difference in mass between the precursor biogenic volatile organic compounds (BVOC) and the HOMs, which will have at least six additional oxygen atoms but, in some cases, considerably more. HOM yields from β-pinene (the second most widely emitted monoterpene; Sindelarova et al, 2014) and isoprene (the most widely emitted BVOC; Sindelarova et al, 2014) are negligible (Ehn et al, 2014). Limonene has emissions at around 25 % of α-pinene (Sindelarova et al, 2014) and is likely to have a higher HOM yield (Ehn et al, 2014;Jokinen et al, 2015) although a much wider range of values have been reported than for α-pinene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations of the composition of molecular clusters present during NPF have highlighted the role that organics may play (Kulmala et al, 2013;Smith et al, 2004). Murphy et al (2006) and Froyd et al (2009) found that larger particles (D p > 0.15 µm) in the UT contained significant organic matter that was likely secondary, which suggests that condensable gas-phase organic compounds are present in the UT.…”
Section: Introductionmentioning
confidence: 99%